1998
DOI: 10.1108/13665629810236264
|View full text |Cite
|
Sign up to set email alerts
|

Total enterprise simulation performance and participant learning

Abstract: Total enterprise simulations are often used and included as graded elements by instructors in business degree capstone "policy courses" under the assumption that their use enriches the learning experience. This suggests a belief that people who perform best in simulations have learned how to play the game better. The studies reported on here attempt to determine and evaluate the relationship between learning and simulation performance. These studies have consistently found that, while simulationrelated learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…They also showed that the students thought the simulation game was superior to a lecture‐centred approach. Washbush and Gosen's () study, in which they compared the before and after scenarios following an enterprise simulation game played by teams of undergraduate business students, showed that students improved their exam score after the simulation. The effectiveness of the simulation game in teaching operations management was demonstrated in Olhager and Persson's () study.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that the students thought the simulation game was superior to a lecture‐centred approach. Washbush and Gosen's () study, in which they compared the before and after scenarios following an enterprise simulation game played by teams of undergraduate business students, showed that students improved their exam score after the simulation. The effectiveness of the simulation game in teaching operations management was demonstrated in Olhager and Persson's () study.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that, as a result of the learning experience, knowledge enhancement had a direct impact on ability enhancement is a very favourable result (cf. Tan & Laswad, 2008) as Washbush and Gosen (1998) did not find such a relationship, although they did note that students in poorer performing teams showed greater learning enhancement whilst Gopinath and Sawyer (1999) linked poor team performance to inconsistency between the strategy and action taken within a simulation. The flip side is that it may be appropriate to consider a supplementary approach to learning for those students who have higher perceived self-efficacy.…”
Section: Discussion Limitations and Implicationsmentioning
confidence: 78%
“…Avramenko (2012) revealed within his United Kingdom (UK) case study of university students that simulations are valuable tools to enhance students' knowledge and therewith abilities for the real-life industry environment; however, at the same time, they require profound planning, preparation and university commitment. Although Washbush and Gosen (1998) found no direct relationship between learning and simulation performance, they demonstrated that students in poor performing teams showed greater learning enhancement. Subsequently, Gopinath and Sawyer (1999) explained how participants understood the importance of a long-term strategic focus; students who performed poorly could link poor performance to an inconsistency between the strategy and action taken within a simulation.…”
Section: Influence Of Knowledge Enhancement On Ability Enhancementmentioning
confidence: 87%
See 1 more Smart Citation
“…It seems like that [students often say in the course] "we made it, it just happened, but we don"t know exactly why/how we got to the end". On the other hand, some explained that performers who struggled a lot learned more than high performers who struggled less (Washbush and Gosenpud, 1993;Wolfe and Chanin, 1993;Washbush and Gosen, 2001). From a pragmatic point of view this can be put another way: given simulation learning in a university setting is a means of attaining grades, the grade-seeking motivation, e.g.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%